Endocrine determinants of incident sarcopenia in middle‐aged and elderly European men. Issue 3 (27th April 2015) - Gielen, Evelien; O'Neill, Terence W.; Pye, Stephen R.; Adams, Judith E.; Wu, Frederick C.; Laurent, Michaël R.; Claessens, Frank; Ward, Kate A.; Boonen, Steven; Bouillon, Roger; Vanderschueren, Dirk; Verschueren, Sabine
Abstract: Background: In men, the long‐term consequences of low serum levels of sex steroids, vitamin D metabolites, and insulin‐like growth factor 1 (IGF‐1) on the evolution of muscle mass, muscle strength, or physical performance are unclear. Moreover, there are no data about the relationship between these hormones and incident sarcopenia defined as low muscle mass and function. The aim of this study was to determine whether the baseline levels of sex hormones, vitamin D metabolites, and IGF‐1 predict changes in muscle mass, muscle strength, physical performance, and incident sarcopenia. Methods: In 518 men aged 40–79 years, recruited for participation in the European Male Ageing Study, total, free, and bioavailable testosterone (T), oestradiol (E), sex hormone‐binding globulin, IGF‐1, 25‐hydroxyvitamin D (25OHD), 1, 25‐dihydroxyvitamin D (1, 25(OH)2 D), and parathyroid hormone were assessed at baseline. Appendicular lean mass (aLM), gait speed, and grip strength were measured at baseline and after a mean follow‐up of 4.3 years. Sarcopenia was defined by the definition of Baumgartner (relative aLM ≤7.26 kg/m 2 ), the International Working Group on Sarcopenia (IWGS), and the European Working Group on Sarcopenia in Older People (EWGSOP). Results: aLM significantly decreased from age 50 years, while gait speed and grip strength significantly decreased from age 70 years. The incidence of sarcopenia by the definitions of Baumgartner, IWGS, and EWGSOP was 8.1%, 3.0%, and 1.6%, respectively. After adjustment for age, centre, body mass index, smoking, and number of comorbidities at baseline, baseline levels of T and vitamin D metabolites were not associated with change in aLM, gait speed, and/or grip strength, while a high baseline level of total E2 was associated with a greater decrease in aLM. In men aged ≥70 years, low IGF‐1 was associated with a greater decrease in gait speed. Baseline endocrine variables were not independently associated with an increased risk of incident sarcopenia by any definition. Conclusions: Low levels of T and 25OHD do not predict loss of muscle mass, gait speed, or grip strength in middle‐aged and elderly community‐dwelling European men. Low IGF‐1 predicts change in gait speed in men aged ≥70 years.